2020
DOI: 10.1155/2020/7283025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Altitude Environment on Driving Safety: A Study on Drivers’ Mental Workload, Situation Awareness, and Driving Behaviour

Abstract: This study aims to analyze the effect of high-altitude environment on drivers’ mental workload (MW), situation awareness (SA), and driving behaviour (DB), and to explore the relationship among those driving performances. Based on a survey, the data of 356 lowlanders engaging in driving activities at Tibetan Plateau (high-altitude group) and 341 lowlanders engaging in driving activities at low altitudes (low-altitude group) were compared and analyzed. The results suggest that the differences between the two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…e result was consistent with the larger mental workload at both PVA and O&L risk points on the road, and it revealed that drivers needed to pay more attention to potential threats in the front of the driving lane to prevent direct collision, which resulted in larger changes in mental workload and driving behaviours. e results of speed choice in this study are consistent with other studies [51,52]. Wang et al did study on hazard handling training method for novice drivers and found that the trained drivers anticipated potential hazards in advance to a larger extent than the untrained, which was indicated by both earlier speed reduction and subjective self-report data when approaching the hazards.…”
Section: Discussionsupporting
confidence: 90%
“…e result was consistent with the larger mental workload at both PVA and O&L risk points on the road, and it revealed that drivers needed to pay more attention to potential threats in the front of the driving lane to prevent direct collision, which resulted in larger changes in mental workload and driving behaviours. e results of speed choice in this study are consistent with other studies [51,52]. Wang et al did study on hazard handling training method for novice drivers and found that the trained drivers anticipated potential hazards in advance to a larger extent than the untrained, which was indicated by both earlier speed reduction and subjective self-report data when approaching the hazards.…”
Section: Discussionsupporting
confidence: 90%
“…High altitude can significantly increase a driver's mental workload and reduce situation awareness, see Wang X, et al [19]. Mental workload is the portion of information processing capacity required to perform a driving task.…”
Section: Drivers Of Vehiclesmentioning
confidence: 99%
“…If the mental workload exceed driver' information processing capacities, it may result in wrong judgement or even improper maneuver, which may cause an accident. [37,38]. The measurement methods of the driver's mental workload include subjective evaluation method, driving task performance method, physiological parameter evaluation method and so on [31,33,[39][40][41].…”
Section: Figure 1 the Four Components Of The Seev Modelmentioning
confidence: 99%